Effects of charge cut-off voltage on the performances of monocrystalline LiNi0.5Co0.2Mn0.3O2/graphite Li-ion cells. (10th April 2019) - Wu, Ziwen; Cao, Changhe; Yan, Xuedong; Zang, Xufeng; Zhao, Ya; Ma, Xingli; Liu, Renhu; Hu, Lina; Jiang, Yingying; Sun, Shanshan
Abstract: Driven by the growing demands of electric vehicles (EVs) and hybrid electric vehicles (HEVs), high energy density Lithium-ion batteries (LIBs) have attracted extensive attentions. Enlarging the charge cut-off voltage (COV) is one of the most effective strategies to improve the energy density of LIBs. In this paper, the electrochemical performances of monocrystalline LiNi0.5 Co0.2 Mn0.3 O2 (MNCM523)/artificial graphite (AGr) pouch Lithium-ion cells charged to 4.30 V, 4.35 V and 4.40 V are studied. The results show that with the increase in the COV, the electrochemical performances including capacity, median voltage and energy density of the cell are all improved with the increases of ohmic resistance simultaneously, while the rate capabilities, high and low temperature (HT&LT) discharge performances and storage performance become slightly worse. The cycle performance of the cells at different charge voltages has no significant difference within 800 cycles but deteriorates after 1000 cycles. The capacity retention gradually decreases with the increasing of COV. Electrochemical impedance spectroscopy (EIS) and incremental capacity analysis (ICA) are adopt to explain the possible reasons of capacity fading, which is considered caused by continuous loss of active materials and lithium inventory due to the deterioration of the electrode-electrolyte interfaces and the increase of charge transfer resistance. The results give a guidance for the design and application. Highlights: The monocrystalline LiNi0.5 Co0.2 Mn0.3 O2 is studied. The electrochemical performances deteriorated with the increase of the charge cut-off voltage. In situ electrochemical impedance spectroscopy and incremental capacity analysis are used.